The Olerud Extensile Anterior Approach for Complex Distal Femoral Fractures: A Systematic Review - Khlopas, Anton; Samuel, Linsen T.; Sultan, Assem A.; Yao, Benjamin; Billow, Damien G.; Kamath, Atul F. (The Journal of Knee Surgery, 2019)
The management of AO/OTA (AO Foundation/Orthopaedic Trauma Association) 33-C3 complex distal femoral fractures presents challenges for orthopaedic surgeons. The extensile anterior approach may be an appropriate alternative treatment technique. The purpose of this systematic review is to (1) evaluate the Olerud approach (extensile anterior approach) for the treatment of 33-C3 complex distal femoral fractures and (2) evaluate postoperative patient outcomes. A systematic literature search was performed to retrieve studies that evaluated the treatment of 33-C3 complex distal femoral fractures. The PubMed database query resulted in 429 studies. Two reviewers independently reviewed the studies, of which six were identified. Patient demographics, AO/OTA fracture, surgical intervention, follow-up duration, clinical outcomes, and postoperative complications were collected and analyzed. The systematic review included six studies reporting on 85 patients (43 males and 42 females); the mean patient age was 45 years (range: 16–101 years). The most common cause of injury was road/traffic accident (51 patients). The mean follow-up time was 26 months (range: 3–72 months). In five studies, the mean time for union was 5.8 months (range: 2–9 months). The three most commonly reported complications were infection (seven [8.2%] patients), failure/malunion (three [3.5%] patients), and delayed tibial tuberosity osteotomy healing (three [3.5%] patients). Seventy (82.4%) patients did not suffer any postoperative complications. Out of 72 patients, 7 (9.7%) had resultant varus/valgus deformity. Overall, 57.1% had excellent/good functional outcomes. Based on the systematic literature review, the extensile anterior approach may be a viable alternative surgical option for 33-C3 complex distal femoral fractures. Given the current literature, more comprehensive and extensive studies need to be performed to ensure the best possible outcome.
Keywords: Olerud; 33-C3 fracture; extensile anterior approach; trauma; distal femoral fractures